Legal and Political Aspects of the De-Armenization of Nagorno-Karabakh: Ethnic Cleansing, Genocide, Forced Displacement or Voluntary Exodus? - Tatikyan, Sossi (ՀՀ ԳԱԱ Հայոց ցեղասպանության թանգարան-ինստիտուտ)
From September 2020 to September 2023, Azerbaijan applied a combination of hard and soft tactics, military and hybrid methods to depopulate Nagorno-Karabakh (Artsakh) of its indigenous Armenian population. Different terms are used by various official, policy and academic circles to describe the de- Armenization of Nagorno-Karabakh. The choice of term often depends on their stance, beliefs, interests and expertise. These terms include “genocide”, “ethnic cleansing”, “forced displacement”, “displacement”, “exodus”, “voluntary exodus”, “migration”, among others. Some also use terms that mock or deny the genocide and ethnic cleansing. This article explores the most accurate terms to describe the de-Armenization of Nagorno- Karabakh. It does this by comparing various perspectives and examining the compliance of the used terms with those implied in international law and relations, as well as their political applicability. The article also revisits the methods and scenarios employed by Azerbaijan, which resulted in the depopulation of Nagorno-Karabakh Armenians. The combined analysis of those aspects and overwhelming evidence shows that the de-Armenization of Nagorno-Karabakh is ethnic cleansing. Legally, it also corresponds to most of the genocide criteria; however, it may be a difficult claim politically and compared with other ongoing conflicts.
Keywords: Genocide